Osteoprotegerin regulates vascular function through syndecan-1 and NADPH oxidase-derived reactive oxygen species. Issue 20 (29th October 2021) - Alves-Lopes, Rhéure; Neves, Karla Bianca; Strembitska, Anastasiya; Harvey, Adam P.; Harvey, Katie Y.; Yusuf, Hiba; Haniford, Susan; Hepburn, Ross T.; Dyet, Jennifer; Beattie, Wendy; Haddow, Laura; McAbney, John; et al.
Abstract: Osteogenic factors, such as osteoprotegerin (OPG), are protective against vascular calcification. However, OPG is also positively associated with cardiovascular damage, particularly in pulmonary hypertension, possibly through processes beyond effects on calcification. In the present study, we focused on calcification-independent vascular effects of OPG through activation of syndecan-1 and NADPH oxidases (Noxs) 1 and 4. Isolated resistance arteries from Wistar–Kyoto (WKY) rats, exposed to exogenous OPG, studied by myography exhibited endothelial and smooth muscle dysfunction. OPG decreased nitric oxide (NO) production, eNOS activation and increased reactive oxygen species (ROS) production in endothelial cells. In VSMCs, OPG increased ROS production, H2 O2 /peroxynitrite levels and activation of Rho kinase and myosin light chain. OPG vascular and redox effects were also inhibited by the syndecan-1 inhibitor synstatin (SSNT). Additionally, heparinase and chondroitinase abolished OPG effects on VSMCs-ROS production, confirming syndecan-1 as OPG molecular partner and suggesting that OPG binds to heparan/chondroitin sulphate chains of syndecan-1. OPG-induced ROS production was abrogated by NoxA1ds (Nox1 inhibitor) and GKT137831 (dual Nox1/Nox4 inhibitor). Tempol (SOD mimetic) inhibited vascular dysfunction induced by OPG. In addition, we studied arteries from Nox1 and Nox4 knockout (KO) mice. Nox1 and Nox4 KO abrogated OPG-induced vascular dysfunction. Vascular dysfunction elicited by OPG is mediated by a complex signalling cascade involving syndecan-1, Nox1 and Nox4. Our data identify novel molecular mechanisms beyond calcification for OPG, which may underlie vascular injurious effects of osteogenic factors in conditions such as hypertension and/or diabetes.